Application of Soil Content Testing on the Growth Media of Water Henna Plants (Impatiens balsamina) with Qualitative Methods - Suslinda Arianti; Dyah Ayu Sri Hartati; M Anshori Aris Widya (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Resistant fertility is very important for plant growth, where soil contains nutrients needed for plant growth and development, soil can be distinguished into two types of soil properties, namely soil chemistry and soil physicality, chemically it can be seen from the value of c-organic, N, and pH, while the physical properties of the soil are related to the type of soil. The water henna plant is one of the potential plants in the Jombang area, the growth of the water henna plant can be maximized by supplying soil nutrients that are still low, one of the potentials is as an antibacterial, and as an economic sector in Jombang City, especially in the dukuh klopo area. To find out the value of the following soil nutrients by entering the previously obtained data into the application, then an application is needed that can calculate the value of soil nutrients. This soil content test application is a new software that can be used to measure soil fertility by entering data or the value of soil nutrient content so that it is in accordance with existing or predetermined standards. This study has the aim of making it easier for the public to know the content in the soil with android-based application media. This research was carried out systematically, which aims to interpret the results descriptively, where this research leads to the creation of an android-based application. Keywords : Android-Based Applications, Soil Content Test Applications, Soil Nutrients, Water henna Plants